Disc haemorrhage associated with an enlarged peripapillary intrachoroidal cavitation in a non-glaucomatous myopic eye: a case report. Issue 1 (December 2015) - Lee, Kyoung; Lee, Eun; Lee, Seung; Kim, Tae-Woo
Abstract Background Disc haemorrhage (DH) is considered a characteristic sign of glaucoma, but its causative mechanism remains to be determined. We present a case of DH that occurred in association with an enlarged peripapillary intrachoroidal cavitation in a non-glaucomatous eye. Case presentation A 35-year-old woman was evaluated for a DH that had been detected during a preoperative examination for myopic refractive surgery. Enhanced depth imaging spectral-domain optical coherence tomography imaging of the optic nerve revealed a peripapillary intrachoroidal cavitation adjacent to the DH. The DH was also present at the 1-year follow-up, but had been completely absorbed at the 2-year follow-up, respectively with an enlargement and shrinkage of the intrachoroidal cavitation and prelaminar tissue schisis. Glaucomatous optic nerve change was not observed during the entire follow-up. Conclusion DH can be caused by mechanical damage to capillaries from microscopic changes in peripapillary tissues such as enlargement of the intrachoroidal cavitation, regardless of the presence of glaucoma.